Improving HPV Vaccination Uptake Among Adolescents in Low Resource Settings: Sociocultural and Socioeconomic Barriers and Facilitators - Xu MA; Choi J; Capasso A; DiClemente RJ (Dove Medical Press, 2024)
Mia Ann Xu,1 Jasmin Choi,1 Ariadna Capasso,2 Ralph J DiClemente1 1Department of Social and Behavioral Sciences, School of Global Public Health, New York University, New York, NY, USA; 2Health Resources in Action, Boston, MA, USACorrespondence: Mia Ann Xu, Email mx489@nyu.eduBackground: Lower- and middle-income countries (LMICs) are disproportionately impacted by human papillomavirus (HPV) and would benefit from implementing the HPV vaccine. In the context of competing health priorities, utilizing scarce domestic infrastructure and human resources for HPV vaccination remains challenging for many LMICs. Given the high benefits of the HPV vaccine, the World Health Organization (WHO) is now encouraging for all countries, particularly LMICs, to introduce HPV vaccines into their routine immunization programs. Understanding the barriers and facilitators to HPV adolescent vaccine programs in LMICs may help strengthen how LMICs implement HPV vaccine programs, in turn, increasing HPV vaccine acceptance, uptake, and coverage.Objective: To identify and assess barriers and facilitators to implementing adolescent HPV vaccination programs in LMICs.Methods: This study comprised a review of literature assessing adolescent HPV vaccination in LMICs published after 2020 from a sociocultural perspective.Results: Overall, the findings showed that LMICs should prioritize increasing HPV vaccine availability and HPV vaccine knowledge, particularly focusing on cancer prevention, as knowledge reduces misinformation and increases vaccine acceptance. Evidence suggests that factors promoting HPV vaccine uptake include fostering low vaccine hesitancy, integrating HPV vaccination as a primary school routine vaccination, and vaccinating both genders. A one-dose HPV vaccine may enable many LMICs to increase vaccine acceptance, uptake, and coverage while controlling financial, infrastructure, and human resource costs.Conclusion: As HPV is one of the leading causes of death in many LMICs, implementing the HPV vaccine may be highly beneficial. Cohesive national HPV vaccine buy-in and understanding the success and challenges of prior LMIC HPV vaccine implementation is crucial to developing effective, efficient, and sustainable HPV vaccination programs.Keywords: HPV, LMICs, vaccine hesitancy, HPV cost, vaccine equity